Octalysis Audit to Analyze Gamification on Kahoot! - Diena Rauda, Ramdania; Dian Sa'adillah, Maylawati; Yana Aditia, Gerhana; Novian Anggis, Suwastika; Muhammad Ali, Ramdhani (Scopus, 2021)
Since its release in 2013, 4.4 billion people around the world have used Kahoot!. Various topics with multiple languages have been made so that there are at least 200 billion games. A very high number for an educational application. Why Kahoot! So interesting? This study aims to analyze the gamification elements found in Kahoot! as a benchmark to create engaging game-based learning in industrial 4.0. The method used is the Octalysis Audit, which examines eight aspects of game psychology: meaning, achievement, empowerment, ownership, social influence,scarcity,unpredictability,and avoidance. The results showed, Kahoot! A value of 441 in Octalysis was obtained. This result shows an excellent balance between positive and negative motivation. Besides, Kahoot also has a balance between Intrinsic and extrinsic motivation.